Large vestibular schwannomas and hydrocephalus: Lessons learnt from a single centre experience - Prakash Nair; Devesh Kumar Singh; Rabi Narayan Sahu; Raj Kumar; Sanjay Behari; Awadesh Kumar Jaiswal; Arun Kumar Srivastava (Indian Journal of Neurosurgery)
Aim The aim of the following study is to analyze the outcome following surgery in 169 patients with large vestibular schwannoma (VS) and to evaluate hydrocephalus as a prognostic factor in patients of the VSs.